Effect of Exchange Rate on Goods and Services in Nigeria - Adurayemi Adu, Cecilia; Uchehara, Chris Chigo; Williams, Adekunle Christopher (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study examined the effect of exchange rate on goods and services in Nigeria with the objectives to analyze the effect of exchange rate fluctuations on prices of domestic goods and to investigate the extent to which exchange rate change has affected the prices of imported goods and services. The primary data were collected through the administration of questionnaire to the respondents. It was found out that the exchange rate has a significant effect on the prices of domestic goods and services as the coefficient of the independent variable is positive showing 0.628; it was established that the exchange rate has an effect on the prices of imported goods and services, as the coefficient of the independent variable is positive (0.428) and the sig value is less than 0.01. It was recommended that the government should fund all the micro, small, and medium scale enterprises in Nigeria through the Bank of Industry in order to have more exports than imports.